Tác động của các nhân tố hiệp moment bậc cao đến tỉ suất sinh lợi: Nghiên cứu thực nghiệm trên Sở Giao dịch Chứng khoán Thành phố Hồ Chí Minh - Nguyễn Phúc , Cảnh; Nguyễn Công , Thành; Nguyễn Văn , Thắng; Nguyễn Hoàng , Phú (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study focuses on identifying the presence as well as effects of higher co-moment involving co-skewness and co-kurtosis on the expected return on Ho Chi Minh City Stock Exchange (HOSE) during 2009–2014. The identification of the impacts of higher co-moment factors may support the estimation of the expected return accurately, and prevent the unexpected risks for investors. By measuring these higher co-moment factors in a five-factor model using the OLS regression technique, we find the statistically significant impacts of co-skewness on the expected return on 15/25 portfolios on the HOSE. The portfolios are formed by the size and market-book value.
Keywords: Higher co-moment; Return; Stock market; HOSE